Applications of Calorimetry - Luis Rivera-Armenta, José; Graciela Flores-Hernández, Cynthia (IntechOpen, 2022)
Calorimetry is used to measure the transfer and exchange of heat. It is a technique that has applications in different research and industrial sectors. It can be applied in kinetic studies as well as to measure physical changes of first- and second-order transitions such as glass transition, melting, and crystallization. It can also be used to evaluate thermodynamic parameters. This book reports on calorimetry in three sections: "Applications in General", "Calorimetry in Materials", and "Calorimetry in Biotechnology".